Synonymy and descriptions in Cerambycinae (Coleoptera, Cerambycidae) from Costa Rica - Galileo, Maria Helena M.; Santos-Silva, Antonio (Zootaxa, 2017)
Hudepohlellus Chemsak & Hovore, 2010, a monotypic genus, is considered a junior synonym of Monneellus Hüdepohl, 1985 and M. semilunatus (Chemsak & Hovore, 2010) is a new combination. Kozlovellus bicolor, a new genus and new species of Rhopalophorini is described from Costa Rica.